Papillary carcinoma of thyroglossal duct cyst with a normal thyroid gland appearance: a case report / Wan Ahmad Amiruddin Wan Hassan ... [et al.] - Wan Hassan, Wan Ahmad Amiruddin; M. Rajet, Khairul Azhar; Md Soleh, Mohd Najeb; Leman, Wan Ishlah (Faculty of Medicine, 2024)
Thyroglossal duct cysts (TGDC) are the most common cause of midline anterior neck mass and are mostly located below the hyoid bone. The gold standard of treatment is the Sistrunk’s operation in which the cyst along with the entire tract and part of the hyoid bone is excised to prevent any remnants and recurrence. Malignant changes in thyroglossal duct cyst are very rare and contributed to about 1-3.2%. Even though the incidence of TGDC carcinoma is rare but it should be one of the differential diagnoses of midline anterior neck mass. Papillary carcinoma of TGDC accounted for about 75-80% of all types of TGDC carcinoma. Papillary carcinoma of TGDC is diagnosed postoperatively following excision of the cyst itself. Due to the rarity of TGDC carcinoma, there is a controversy regarding the need for total thyroidectomy in the management of TGDC malignancy.